Zn-Doped SnO2 Compact Layer for Enhancing Performance of Perovskite Solar Cells - Chenjun Yang; Mengwei Chen; Jiaqi Wang; Haifei Lu (International Journal of Photoenergy)
Perovskite solar cells (PSCs) have been developing rapidly since they were discovered, and their excellent photoelectric properties have attracted wide attention from researchers. The compact layer is an important part of PSCs, which can transport electrons and block holes. SnO2 is an excellent and commonly used electron transport layer (ETL) material, and doping modification is an effective way to improve performance. Here, Zn with a similar radius to Sn has been introduced to the doping of the SnO2 compact layer to achieve the purposes of conductivity enhancement of the compact layer and followed photoelectric performance improvement of the device. Zn-SnO2 compact layers with different doping concentrations were prepared and applied to mesoporous architecture PSCs. When the doping content was 5%, the power conversion efficiency (PCE) of the device based on the Zn-SnO2 compact layer has increased from 9.08% to 10.21%, with an increase of 12.44%. The doping of SnO2 promotes its application in low-cost PSCs.